Factors influencing infant basic immunization uptake at Bestari Community Health Center, Medan - Pahala Maringan Jubel Simangunsong; Herbert Wau; Lincewan Lestari Gulo; Riky Suherman Simanjuntak; Claudia Tanamal; Andri Hidayat; Muhammad Rizal Rezaldi; Jeff Loren; Rizki Arviandi (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Immunization is one of the most effective public health interventions for preventing infectious diseases and reducing mortality rates. However, complete basic immunization coverage in Indonesia, particularly in North Sumatra, remains suboptimal. This study aimed to analyze the relationship between maternal characteristics (age, education, employment, knowledge, and attitudes) and the provision of complete basic immunization for infants at the Bestari Community Health Center in Medan. Methods: The research employed an analytical survey with a cross-sectional approach involving 60 mothers visiting integrated health posts in November 2022. Data were collected via questionnaires and analyzed using the chi-square test. Results: Results indicated significant associations between maternal age (p = 0.002), education level (p = 0.003), employment status (p = 0.000), knowledge (p = 0.000), and attitudes (p = 0.000) with infant immunization completeness. Conclusion: The study concludes that sociodemographic factors and maternal understanding play crucial roles in immunization coverage.